Penyelesaian Sengketa Waris Tanah Pusako Tinggi sebagai Tanah Adat melalui Pengadilan Agama Kelas 1a Padang - Iasra, Rizki Fajri; Yaswirman, Yaswirman; Yasniwati, Yasniwati (Universitas Ekasakti, 2023)
Indonesia is a country that has ethnic and cultural diversity, this becomes an advantage as well as a weakness if the government is not able to develop rules and policies that represent the needs of its citizens.This can be seen in the system of inheritance distribution in Indonesia which adheres to three systems of inheritance law, namely Customary Inheritance Law, Islamic Inheritance Law and Indonesian Civil Inheritance Law. The legal system of heirs is influenced by the kinship system owned by a region. Indonesia knows 3 (three) kinship systems, namely matrilineal, patrilineal and parental kinship systems. The matrilineal kinship system sees the maternal lineage, the patrilineal kinship system sees the paternal lineage, and the parental kinship system sees the maternal and maternal lineage. The Minangkabau are a growing tribe in West Sumatra Province, where the people adopt a matrilineal kinship system, a kinship system and the Inheritance is inherited according to the lineage of the Mother. This means that boys and girls and their families, including racism mother, who inherited the property. Basic on decision No 292 / K / Ag / 2019 that the origin of the land on the decision proved to be the executor of Appeal, but still devolved court Religion. This is contrary to the West Sumatra Regional Regulation No. 16 of 2008 Article 12 paragraph 2 on Ulayat Land and its Use, if the peace decision is not accepted by the disputing party as referred to in paragraph 1 then the disputing parties may take the matter to the District Court. It is clear that the regulation states that the Religious Court does not have the authority to examine and adjudicate matters a quo. Inheritance of High Estate in Minangkabau is only regulated in the provisions of customary law which sometimes when there is a dispute over the division of heirs of High Estate, often overrides the provisions of customary law in resolving disputes so that in its application some rules even make the essentials of High Estate reduced or even lost.